Peningkatan Literasi Anak dan Literasi Keuangan melalui Kegiatan Membaca dan Mewarnai - Moch. Fikriansyah Wicaksono; Imarotus Suaidah; Galuh Indah Zatadini; Firda Alfiani; Sylfia Rizzana (Yayasan Literasi Sains Indonesia, 2025)
Child literacy and financial literacy are important skills that need to be instilled from an early age to prepare children for future life challenges. This activity aims to improve children's literacy and introduce the basic concept of financial literacy through reading and coloring activities. The activity was carried out at the Kraton Village Library, Yosowilangun District, Lumajang Regency in August 2025, involving children from early childhood to elementary school. In this activity, children were given a storybook with the theme of financial literacy, followed by coloring activities with pictures related to the stories they read, such as pictures of piggy banks and money. The results of the activity showed that children not only improved their reading skills, but also gained a basic understanding of money management, such as saving and managing a simple budget. The involvement of parents in accompanying children also makes a positive contribution to strengthening the understanding of financial literacy at home. The success of this activity shows the importance of the role of village libraries as literacy centers that can integrate literacy and financial literacy. It is hoped that this activity can be used as a model to improve children's literacy and financial literacy in other regions in Indonesia. Child literacy and financial literacy are important skills that need to be instilled from an early age to prepare children for future life challenges. This activity aims to improve children's literacy and introduce the basic concept of financial literacy through reading and coloring activities. The activity was carried out at the Kraton Village Library, Yosowilangun District, Lumajang Regency in August 2025, involving children from early childhood to elementary school. In this activity, children were given a storybook with the theme of financial literacy, followed by coloring activities with pictures related to the stories they read, such as pictures of piggy banks and money. The results of the activity showed that children not only improved their reading skills, but also gained a basic understanding of money management, such as saving and managing a simple budget. The involvement of parents in accompanying children also makes a positive contribution to strengthening the understanding of financial literacy at home. The success of this activity shows the importance of the role of village libraries as literacy centers that can integrate literacy and financial literacy. It is hoped that this activity can be used as a model to improve children's literacy and financial literacy in other regions in Indonesia.